Physiological ecology and vulnerability to climate change of a microendemic, habitat-specialist lizard in a tropical dry forest of Mexico - Francisco Javier Muñoz-Nolasco; Diego Miguel Arenas-Moreno; Fabiola Judith Gandarilla-Aizpuro; Adán Bautista-del Moral; Rufino Santos-Bibiano; Donald B. Miles; Fausto Roberto Méndez-de la Cruz (Climate Change Ecology, 2023)
The role of physiology on habitat specialization in terrestrial ectotherms constitutes a rarely addressed topic, despite the fact that habitat specialization often involves the coadaptation of multiple physiological traits, which in turn may confer a higher vulnerability to climate change. Here we documented aspects of the thermal and hydric physiology of Sceloporus macdougalli, a lizard restricted to granite boulders in a tiny area of a tropical dry forest of Mexico, and estimated its vulnerability to climate change. We aimed to determine the physiological and behavioral adjustments used by this species to cope with a striking seasonal environment, to elucidate whether ecophysiology could help explain its habitat specialization, microendemicity, and how increasing environmental temperatures will restrict activity of this species. The effectiveness of thermoregulation and indications of water conservation strategies changed markedly over seasons. As expected, granite boulders and associated vegetation were more suitable for thermo- and hydroregulation than surrounding (and unoccupied) habitat. However, our model indicated that by 2041-2060 climate change will restrict activity of this species, enhancing its threat of extinction. These results highlight the importance of granite microhabitats for the thermal and water relations of S. macdougalli, in the context of climate change, and suggest that the current habitat and range restriction of the species might be an outcome of its physiology, thus demanding urgent actions to preserve the species from extinction.